Daur Ulang Sampah Plastik Melalui Kreatifitas Kerajinan Tangan Di Teras Baca Rejosari - Fitriyanti; Aulia Putri Rahmawati; Dhita Sukma Anggraeni; Rosandra Firdi Silviana; Syalwa Anggun Indiani; Yuwanti (LPPM AN Nuur, 2021)
Background: Plastic waste is the most waste and difficult to decompose even takes decades to decompose and this waste is very dangerous to the community and the environment because it is composed of chemicals, but many of the behavior of people who still throw plastic waste carelessly so that it has a negative impact on the environment, so education is needed in the management of useful plastic waste. Aims: provide craft creativity training through recycling plastic waste. Methods: survey analasis of the situation and implementation and training. Results: Through the devotion and creation of plastic waste processing creations into useful goods children understand more about the use of unused goods around them and create more innovative creations from plastic waste. Conclusion: the creativity of handicrafts from waste can increase concern for plastic waste management.